2019
DOI: 10.1504/ijbg.2019.100258
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatives and crisis: economic dynamics in Italian context

Abstract: This paper focuses on the situation in Italy with specific reference to cooperatives. It aims to analyse their economic situation -represented by two profitability ratios (ROI, ROE) -during the decade 2004-2013. It aims to tests the impact of crisis, geographical area and belonging business sector. Starting from secondary data on AIDA database (at the end 1,446 cooperatives), the trend analysis and analysis of variance (ANOVA) have been used. The findings show, first of all, that the profitability of cooperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…This is the case, for example, in the tanning industry (Migliaccio and Arena, 2018b) or for hotels (Migliaccio, 2018). This study, on the contrary, confirms the decreasing profitability already registered for the only Italian cooperatives operating in the primary sector (Fusco and Migliaccio, 2016b, 2019).…”
Section: Summary Conclusion and Implicationssupporting
confidence: 83%
See 3 more Smart Citations
“…This is the case, for example, in the tanning industry (Migliaccio and Arena, 2018b) or for hotels (Migliaccio, 2018). This study, on the contrary, confirms the decreasing profitability already registered for the only Italian cooperatives operating in the primary sector (Fusco and Migliaccio, 2016b, 2019).…”
Section: Summary Conclusion and Implicationssupporting
confidence: 83%
“…Also, the third hypothesis (H3) is partially unconfirmed because, considering the territorial economic imbalances that characterize Italy, they did not have different effects on the profitability of the farms located in the different areas, with some exceptions. Also, in this case, there are similarities for studies conducted for agricultural cooperatives (Fusco and Migliaccio, 2016b, 2019). The study showed that differences in profitability exist and, in some cases, the ANOVA test has allowed us to find some of them also with a certain statistical importance.…”
Section: Summary Conclusion and Implicationssupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, given this ambiguous evidence in the literature, which can represent an intriguing gap to explore, the extent to which cooperatives can perform better than IOFs is the scope of the current research; naturally, as the presence of cooperatives in all economies and especially in the agri-food sector is so vast, as mentioned above, it was necessary to detect a specific context of investigation to pursue this goal. In the agricultural sector, Italy has a large and well-developed system of cooperatives that play a relevant role, as they produce more than a third of the total agricultural production; approximately 5,000 cooperatives operate in Italy, with a total turnover of approximately 40 billion euros and more than 90,000 employees (Italian Agricultural Cooperation Observatory, 2017; Fusco and Migliaccio, 2019).…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%